Gigantic hip mass as the initial presentation of hyperphosphatemic familial tumoral calcinosis - Krishnan, Surya; Murali, Anjali; Keechilat, Pavithran (Archive of Oncology, 2026)
Introduction: Hyperphosphatemic familial tumoural calcinosis (HFTC) is a rare autosomal recessive disorder characterised by ectopic calcium phosphate deposition around the joints due to mutations affecting phosphate regulation.Case outline: We report a 7-year-old boy who presented with hip pain and swelling, mimicking malignancy. Imaging revealed a large lobulated soft tissue mass involving the left iliac fossa and pelvic musculature. The FDG-PET and MRI findings suggested a neoplastic lesion, but the FNAC revealed only calcific debris. Biochemical analysis revealed elevated serum phosphorus levels and low PTH. Whole-exome sequencing identified a homozygous likely pathogenic mutation in GALNT3 (c.840T>A; p.Cys280Ter). Medical management included phosphate binders and acetazolamide. Despite initial improvement, recurrence occurred one year later. Surgical options were deemed high-risk and conservative treatment was continued.Conclusion: This case highlights the importance of considering HFTC in the differential diagnosis of calcified soft tissue masses in children and the role of genetic testing in diagnosis and management.